The Effect of Artificial Intelligence Use and Professional Skepticism on Audit Quality in Public Accounting Offices in DKI Jakarta - Kholidah; Ida Rosnidah (Majapahit Journal of Islamic Finance and Management, 2026)
The development of Artificial Intelligence in auditing practices has driven significant changes in the financial statement audit process, particularly in Public Accounting Firms in urban areas such as Jakarta. This study aims to analyze the influence of the use of Artificial Intelligence and auditors' professional skepticism on audit quality. The research method used is a quantitative approach with data collection through questionnaires distributed to auditors at Public Accounting Firms in Jakarta, then analyzed using multiple regression analysis. The results show that the use of Artificial Intelligence and auditors' professional skepticism have a positive and significant effect on audit quality, both partially and simultaneously. This finding suggests that the implementation of Artificial Intelligence-based audit technology needs to be balanced with auditors' professional skepticism to maintain optimal audit quality. Thus, it can be concluded that the integration of Artificial Intelligence technology and strengthening auditors' professional skepticism are important factors in improving audit quality at Public Accounting Firms in Jakarta.